Tubular enteric duplication presenting as jejuno-colic fistula in a 38 years old adult - N., Chandhana Vishal; Ahmed, Sameer; Pai, B. Srinivas (International Surgery Journal, 2020)
Colo-enteric fistula is a rare entity, malignancy being the commonest cause. Both adenocarcinoma and rarely lymphoma have been known to cause it. Benign jejuno-colic fistulas are mostly secondary to tuberculosis or inflammatory bowel disease. Here we present a case of a young adult male, who presented with altered bowel habits. Colonoscopy and oesophago-gastro-duodenoscopy (OGD) revealed a fistulous tract between the proximal jejunum to the splenic flexure of colon. Surgery revealed a small fistulous connection between the above-mentioned parts of the bowel about 1cm long. Histopathology demonstrated it to have all the layers of the intestinal anatomy, hence indicating a possibility of congenital aetiology, probably enteric duplication of communicating tubular variety.